PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN MANAJEMEN LABA TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI MEDIASI (PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023) - Chaterina Sherly Meliana; Justita Dura; Agus Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the influence of corporate social responsibility and earnings management on company value through company financial performance. This research uses a quantitative-causal type of research. In this study, researchers collected data through the Indonesian Stock Exchange website and the company's official website. This research uses Smart PLS3 to process data and the research was carried out in September – December 2024. The tests carried out in this research were financial analysis, multicollinearity test, R square test, F square test and path analysis hypothesis test. The results of this research show that corporate social responsibility, earnings management and financial performance have an influence on company value and corporate social responsibility has an influence on financial performance but earnings management has a negative effect on financial performance and financial performance is able to mediate between corporate social responsibility and company value but unable to mediate the effect of earnings management on firm value.